Could Bat Cell Temperature and Filovirus Filament Length Explain the Emergence of Ebola Virus in Mammals? Predictions of a Thermodynamic Model. Issue 6 (26th September 2016) - Gale, P.
Summary: The host reservoir of Zaire ebolavirus (EBOV) remains elusive. One suggestion is that EBOV emerges in mammals when the precursor virus jumps from mayflies (or other riverine insects) to insectivorous bats. However, this does not fit with the current view that filoviruses cannot infect arthropods. Here, it is first argued that the evidence that arthropods are refractory is not definitive. Second, it is proposed that a combination of filovirus filament length and the high temperature ( 42°C) experienced by an insect virus ingested by a flying bat, together with the large number of insects eaten by bats (e.g. during an ephemeral mass emergence of mayflies), facilitate jumping the species barrier. The length of a filovirus filament is related to the number of genome copies (GC). Predictions from a preliminary thermodynamic model developed here suggest that filament length could greatly affect EBOV infectivity to mammalian cells with infectivity peaking for filaments of a certain length. Importantly, the infectivity to mammals of even short filaments may be more than one million‐fold higher than that for the single GC virion. Third, it is proposed that at the high temperature within the bat, the phospholipid phosphatidylserine in the virus envelope promotes filament formation through fusion of single GC particles within the ingested insect, thus hugely increasing their infectivity to bats. Forth, according to the thermodynamic model, increasing the temperature from 27°C (insect cell temperature at average air temperature in Guinea, West Africa) to 42°C (bat) could increase the affinity of the filaments for bat cells by 1–2 orders of magnitude, while having no effect on the binding affinity of the single GC virions. The thermodynamic model developed here is supported by the counterintuitive observation that high glycoprotein densities on the EBOV surface reduce its infectivity in contrast to other viruses such as HIV.